(untitled) (Revista Rupturas, 2023)
This article is part of a broader sociological investigation and on this research what is intended is to studies the narration of television advertising; which is produced to persuade the poor informal and impoverished working classes to consume through informal credit in Costa Rica. Particularly, this academic-scientific paper analyzes advertising, which is conceived as cultural artifacts produced by the advertising industry, then these were the object of a critical political analysis of the image. One of the most important conclusions that the study yielded was the understanding that advertising, as a powerful social fact, operates in a cultural-symbolic key and as an ideological suture in the face of a social, economic and culturally unequal daily life. In addition to advertising as an artifact, a cultural instrumentalized certain mythical elements of the Costa Rican idiosyncrasy to reproduce the capitalist cultural system and also reproduce and update certain parts of the country’s nationalist myth